Development of the test kit for detection of SARS-CoV-2 antibodies in sera of susceptible animals - M. A. Volkova; N. G. Zinyakov; P. S. Yaroslavtseva; I. A. Chvala; T. S. Galkina; D. B. Andreychuk (Ветеринария сегодня)
The novel coronavirus infection COVID-19, caused by the SARS-CoV-2, has triggered a pandemic, and has also been reported in animal populations – in farm minks, dogs and felines: domestic cats, lions and tigers. The susceptibility of some animal species to the SARS-CoV-2 has been proven by experimental infection. Serological methods are effectively used to detect the infection in animals. Currently, methods such as neutralization test, immunofluorescence assay and enzyme-linked immunoassay are used to detect antibodies to coronaviruses. Thanks to these studies, a test kit was developed based on an indirect enzyme-linked immunoassay to detect the SARS-CoV-2 antibodies in sera of susceptible animals. The use of a purified concentrated inactivated virus as an antigen allows the detection of antibodies to various SARS-CoV-2 immunodominant proteins (S and N). The reaction conditions were optimized, and a positive-negative threshold was established by testing of 154 negative sera from animals of six species (ferrets, minks, foxes, arctic foxes, cats and dogs). The method reproducibility analysis showed that the average value of the variation coefficient did not exceed 7%, which is an acceptable value. The specificity and sensitivity of the neutralization test, when testing 30 sera from ferrets was 100 and 92.6%, respectively. The high diagnostic sensitivity and specificity shown by testing of 50 serum samples from minks, foxes, cats and dogs with different immune status, allow us to recommend the developed test kit for screening and monitoring tests and post-vaccination immunity control.